Cabbage Commodity Agribusiness Management - Tonkham Phrommany; Jessica Philavong (Journal La Lifesci, 2021)
The purpose of this research is to assess and evaluate the performance of the agribusiness system in relation to the Cabbage crop. The Agribusiness System is comprised of four (four) components: In the first place, there is the upstream agricultural industry. The marketing system that has been established is an ordinary marketing system, meaning that it provides complete autonomy to every marketing agency and producer farmer in the conduct of their individual enterprises. Supply networks for cabbage in general tend to be driven by the dynamics of supply and demand in the market, and are still predominated by conventional supply chains whose primary outlets are traditional marketplaces